2019
DOI: 10.1097/mpg.0000000000002466
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Effects of Mitomycin C Infiltration for Caustic Oesophageal Strictures in Children

Abstract: Objectives: The aim of this study was to investigate the efficacy and safety of endoscopic local infiltration of mitomycin C (MMC) after oesophageal dilation for children suffering from refractory postcorrosive oesophageal stricture (OS). Methods: Children referred to Cairo University Specialized Paediatric Hospital with refractory postcorrosive OS during the period from March 2016 to August 2017 were included in this study. MMC was infiltrated endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A French multicenter study showed a 67% success rate in their 39 patients with a significant decrease in number of dilatations prior (102) and post MMC application (17) (51). Wishahy et al observed a significant improvement in dysphagia score in their 17 children treated with MMC (54). In general, patients received an MMC dose between 0.1 and 1 mg/ml.…”
Section: Use Of Mitomycin C (Mmc) Following Dilationmentioning
confidence: 99%
See 1 more Smart Citation
“…A French multicenter study showed a 67% success rate in their 39 patients with a significant decrease in number of dilatations prior (102) and post MMC application (17) (51). Wishahy et al observed a significant improvement in dysphagia score in their 17 children treated with MMC (54). In general, patients received an MMC dose between 0.1 and 1 mg/ml.…”
Section: Use Of Mitomycin C (Mmc) Following Dilationmentioning
confidence: 99%
“…Various etiologies can cause esophageal strictures and stenosis in children, with caustic, anastomotic, congenital, GERD, and eosinophilic esophagitis being the most common (22,(49)(50)(51)(52)(53)(54). To date, there are various endoscopic treatment options, of which endoluminal balloon dilatation is probably the most useful and safe.…”
Section: Advances In Endo-dilatation For Treatment Of Esophageal Sten...mentioning
confidence: 99%
“…Recently, intralesional administration of MMC was found to be effective and safe in 17 children with refractory caustic strictures in the short term [40].…”
Section: Mytomicin C: Intralesional and Topicalmentioning
confidence: 99%